STUDY OF THE ACTION OF BINARY ANTIOXIDANT COMPOSITIONS WITH ASCORBIC ACID ON MODEL SYSTEMS - ЄФІМОВА, І. В.; СМИРНОВА, О. В.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2025)
Abstract. The issue of creating antioxidant compositions with improved and more effective properties has become relevant in recent years due to the increasing prevalence of influenza, pneumonia and other respiratory diseases, the mechanism of which is based on free radical processes. The combined use of antioxidants contributes to more effective inhibition of free radical oxidation of membrane lipids (ascorbic acid with vitamin E, A, flavonoids, carotenoids, glutathione). Understanding the exact characteristics and properties of natural bioprotectors deepens the understanding of the basic mechanisms of interaction between antioxidants. The use of model systems makes it possible to study complex and multifaceted oxidation processes in which ascorbic acid participates in vivo. As model systems, it is convenient to use radical-chain oxidation of organic substrates in an aprotic environment - a process in which all elementary stages have been almost perfectly studied and their kinetic parameters have been obtained. Purpose. To establish the physicochemical regularities of oxidation processes in the presence of antioxidant compositions of ascorbic acid with an oxygen radical anion, humic and hematomelanic acids, as well as to identify the possibility of regulating the antioxidant and prooxidant properties of these supramolecular inhibitory systems in radical chain processes. Methodology. The initiated oxidation of cumene in an aprotic medium in the presence of antioxidant compositions of ascorbic acid with an oxygen radical anion, humic and hematomelanic acids was investigated by measuring the change in absorbed molecular oxygen. Findings. In the presented work, based on the initiated radical-chain oxidation process of cumene in an aprotic environment (model system), the antioxidant effect of binary compositions of ascorbic acid with some representatives of inhibitors of natural origin was studied. The peculiarities of the oxidation course of the model system in the presence of humic and hymatomlanic acids were studied, and their antioxidant properties were proven. An increase in the inhibitory effect of humic substances on the oxidation process of cumene was observed with an increase in their concentration in the model system. It was also proven that with an increase in the concentration of these binary compounds in the studied system, the protective efficiency increases. The effect of the supramolecular composition of ascorbic acid and the oxygen radical anion on the oxidation process of the model system was studied. It was shown that the combined effect of ascorbic acid and superoxide anion is inhibitory, and this effect increases with an increase in the concentration of the antioxidant complex in the studied system. Originality. It was found that during the oxidation of the model system, the complex inhibitory effect of the antioxidant composition of ascorbic acid and humic substances from brown coal has an additive effect. The induction effect, caused by the presence of the antioxidant composition of ascorbic acid with superoxide anion, is synergistic in nature, for which the optimal ratio of the amount of oxygen radical anion and ascorbic acid in the antioxidant composition for maximum synergistic effect was found. Practical value. The mediator participation of the oxygen radical anion in the oxidation processes of the model system in the presence of ascorbic acid has been experimentally confirmed, which can contribute to the understanding of the mechanisms of many pathological conditions caused by free radical oxidation processes. The relevance of using the given model system for further studying the antioxidant action of humic substances and antioxidant compositions based on them has been proven.